The Influence of the Number of Collection Centers, Areca Nut Prices in Jambi, and Production Volume on Areca Nut Exports in Jambi Province: English - Lili Febriyani; Rahma Nurjanah; Dearmi Artis (Cita konsultindo, 2025)
This study aims to analyze: (1) the development of the number of collection centers, areca nut prices in Jambi, and production volume in relation to areca nut exports in Jambi Province; and (2) the influence of the number of collection centers, areca nut prices, and production volume on areca nut exports in Jambi Province. The research uses secondary data obtained from the Central Bureau of Statistics (BPS) of Jambi Province and the Jambi Provincial Plantation Office for the period 2005–2023. The analytical method employed is multiple linear regression with the assistance of Eviews 10 software. The results show that areca nut exports experienced fluctuations with an average growth rate of 17.58%, the number of collection centers by 6.51%, areca nut prices by 7.39%, and production volume by 19.24%. The regression results indicate that the number of collection centers and areca nut prices have a significant effect on areca nut exports, while production volume has no significant effect.